Flavoproteins as native and genetically encoded spin probes for in cell ESR spectroscopy - Timothée Chauviré; Siddarth Chandrasekaran; Robert Dunleavy; Jack H. Freed; Brian R. Crane (Nature Communications)
Abstract Flavin cofactors are attractive Electron Spin Resonance (ESR) probes for proteins because cellular reductants and light can generate their semiquinone states. Here, we use ESR spectroscopy to study the bacterial transmembrane aerotaxis receptor (Aer) in its native Escherichia coli membrane environment. Optimization of the spectroscopic (electronic relaxation times) and cell growth (isotopic labeling) conditions allow for measurements of Aer with its partners - the histidine kinase (CheA) and the coupling protein (CheW) - in native signaling arrays. Continuous-wave ESR measurements at room temperature show a rigid Aer flavin immobilized in the cofactor pocket and Q-band electron nuclear double resonance (ENDOR) measurements identify a predominant anionic semiquinone radical state in cell. Q-band four-pulse double electron-electron resonance (4P-DEER) measurements indicate a 4.1 nm distance between the two flavins of an Aer homodimer, consistent with previous in vitro measurements, but also reveal additional separations in cell indicative of chemoreceptor arrays, not previously observed for Aer. For general application, we further develop a genetically encoded Light-Oxygen and Voltage (LOV) domain for incorporation into target proteins as an ESR probe of structural properties in cell. This approach provides a framework to elucidate protein oligomeric states and conformations that are difficult to reproduce in vitro.